2018
DOI: 10.7717/peerj.4269
|View full text |Cite
|
Sign up to set email alerts
|

Authorial and institutional stratification in open access publishing: the case of global health research

Abstract: Using a database of recent articles published in the field of Global Health research, we examine institutional sources of stratification in publishing access outcomes. Traditionally, the focus on inequality in scientific publishing has focused on prestige hierarchies in established print journals. This project examines stratification in contemporary publishing with a particular focus on subscription vs. various Open Access (OA) publishing options. Findings show that authors working at lower-ranked universities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 59 publications
2
48
0
1
Order By: Relevance
“…The Open Scholarship Ranking (Fan and Liu 2016) identifies a significant correlation between the Open Scholarship achievements of Chinese Universities and the results of existing comprehensive university rankings. This is consistent with recent work on stratification within OA the literature relating to global health research, which finds that authors working at lower-ranked universities are less likely to choose journals that involve an Article Processing Charge and more likely to publish in closed or paywalled journals (Siler et al 2018). This may be because comprehensive university rankings relate closely to the resources available within an institution.…”
Section: Discussion and Conclusion: Diversity Complexity And Opportusupporting
confidence: 77%
“…The Open Scholarship Ranking (Fan and Liu 2016) identifies a significant correlation between the Open Scholarship achievements of Chinese Universities and the results of existing comprehensive university rankings. This is consistent with recent work on stratification within OA the literature relating to global health research, which finds that authors working at lower-ranked universities are less likely to choose journals that involve an Article Processing Charge and more likely to publish in closed or paywalled journals (Siler et al 2018). This may be because comprehensive university rankings relate closely to the resources available within an institution.…”
Section: Discussion and Conclusion: Diversity Complexity And Opportusupporting
confidence: 77%
“…Unfortunately, the irregular distribution of resources throughout the world, and correspondingly in 111 academia, creates a bubble where higher ranking institutions have more access to expensive, higher impact 112 journals, while lower ranking institutions are forced to publish in less expensive or closed access journals 113 (Siler, et al 2018). The alternative is that authors from developing countries have to pay the prices of 114 developed countries in order to have access to higher impact journals (Ellers, 2017).…”
Section: Journals 110mentioning
confidence: 99%
“…This is increasingly more problematic for 118 scientific output, as independent researchers with no institutional affiliation have been on the rise over the 119 past decade (ElSabry, 2017). However, evidence suggests that the researchers being put on the backburner, 120 are no less reliable than the privileged few institutions which have the advantages to publish in high impact, 121 high APC journals (Brembs, 2018;Brembs, 2013;ElSabry, 2017;Siler, et al 2018).…”
Section: Journals 110mentioning
confidence: 99%
See 1 more Smart Citation
“…This provides evidence of national or regional effects on publication cultures that lead to open access. Meanwhile, Siler et al (2018) showed that, for the field of Global Health, lower-ranked institutions are more likely to publish in closed outlets. They suggest this is due to the cost of article processing charges showing the importance of considering institutional context when examining open access performance.…”
Section: Introductionmentioning
confidence: 99%